Fools Die - Puzo, Mario (Pan Books)
Encompassing America's golden triangle of corruption, New York, Hollywood, and Las Vegas, this novel involves high rollers and big-time hustlers in a vibrant atmosphere of greed, lust, violence and betrayal.
Keywords: Brothers -- United States -- Gambling -- Prostitution